2008
DOI: 10.1590/s0100-879x2008001200017
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength but not functional capacity is associated with plasma interleukin-6 levels of community-dwelling elderly women

Abstract: The association of plasma interleukin-6 (IL-6) levels, muscle strength and functional capacity was investigated in a crosssectional study of community-dwelling elderly women from Belo Horizonte, Brazil. Elderly people who present controlled chronic diseases with no negative impact on physical, psychosocial and mental functionality are considered to be community-dwelling. Psychological and social stress due to unsuccessfully aging can represent a risk for immune system disfunctions. IL-6 levels, isokinetic musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
2
14
0
2
Order By: Relevance
“…In this respect, the genes involved in regulating the inflammatory process, which increases with age, may contribute to individual variation in plasma cytokine levels and muscle strength in the elderly. However, despite evidence pointing at the action of IL-6 as one of the factors related to the reduction of muscle mass and muscle strength (sarcopenia) (1,(20)(21)(22) and the importance of genetic variation in the regulation of this cytokine, studies investigating the impact of the -174 G/C polymorphism of the IL6 gene on the variables of muscle performance are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the genes involved in regulating the inflammatory process, which increases with age, may contribute to individual variation in plasma cytokine levels and muscle strength in the elderly. However, despite evidence pointing at the action of IL-6 as one of the factors related to the reduction of muscle mass and muscle strength (sarcopenia) (1,(20)(21)(22) and the importance of genetic variation in the regulation of this cytokine, studies investigating the impact of the -174 G/C polymorphism of the IL6 gene on the variables of muscle performance are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns com grupo de estudo formado por jovens do sexo feminino 1,21,[23][24][25][26][27] , jovens do sexo masculino 19,28,29,30 , e outros por indivíduos idosos de ambos os sexos 5,7,[12][13][14][15][16]20,31,32 . Já outros estudos foram voltados para a população de indivíduos com patologias 2,6,8,33,34,35 e em pós-operatório 9,36 .…”
Section: Resultsunclassified
“…18,27,28 . Quanto a frequência de avaliações, uma única avaliação foi a mais recorrente 2,3,4,6,8,9,[11][12][13][14]16,28,[30][31][32][33][34][35][36][37][38] . Outros estudos abordaram avaliações pré e pós-intervenção, sendo estas treinamento de força 7,10,17,20,25,26 ; eletroestimulação 24 , suplementação 23 e alongamento 1,29 .…”
Section: Resultsunclassified
“…Unlike functional tests of gait speed and sitting and standing, there was no correlation (26) demonstrated, indicating that functionality encompasses a harmonious integration of various sensory motor systems and not only muscle tissue. Furthermore, results of the study by Oliveira et al (26) indicated a catabolic action of inflammatory cytokines on muscle fibers. A study by Lustosa et al (27) that assessed muscle strength with an isokinetic dynamometer (considered the gold standard tool for this measure) revealed an association between increased inflammatory cytokines and low muscular and functional performance in elderly individuals.…”
Section: Discussionmentioning
confidence: 95%
“…Decreased HGS has been previously identified as strong biomarker for aging (12,16,20), indicating a negative impact of muscle strength loss on functional capacity (26). This measure provides an approximation of total body muscle force as it correlates with elbow flexion strength, extension force of the leg, and trunk strength (9).…”
Section: Discussionmentioning
confidence: 99%